Evaluation survey on training of community-based child growth monitors and promoters in Zambia - Zulu, Caroline; Michelo, C; Ngoma, C. M (International Journal of Nursing Research, 2023)
Background: CCGMP is a relevant complementary activity for many of the actions and interventions that need to be undertaken for the proper growth of children, especially in the under privileged communities, like Zambia. Design and Methods: This research applied a cross-sectional survey and this publication shows findings from the quantitative method, using scheduled questionnaire that was applied to collect data. One-to-one interview method to fill in the questionnaire was used because of the respondents’ level of education, as most were semi-literate. The cross Sectional Survey was applied to facilitate evaluation of the training programmes for CCGMPs in order to identify possible gaps between the curriculums, training process and practices that were recommended training and implementation of the CCGMP programme. Results: Study significantly revealed that training of CCGMPs was inadequate because they as they spent very short duration, not as recommended by the National Food and Nutrition Commission curriculum (NFNC 2000), questioning extent to which topics were covered both theoretically and practically. The practical part suffered the most as they spent not only a shorter duration but also lack of supervision and follow up after training. Due to the limited time spent on training, learning from these programs was inadequate. In practice, weighing methods were inconsistent and Nutrition counselling to the caregivers/mothers was lacking at almost all of the study sites. Conclusion: This study proves that CCGMPs were inadequately trained, despite them making great contribution (97%) towards monitoring of the Zambian children. This could be a major contributor their poor performance in implementing services, consequently leading to persistently high infant and child mortality rates.